What does best evidence tell us about robotic gait rehabilitation in stroke patients: A systematic review and meta-analysis - Bruni, Maria Federica; Melegari, Corrado; De Cola, Maria Cristina; Bramanti, Alessia; Bramanti, Placido; Calabrò, Rocco Salvatore (Journal of clinical neuroscience, 2018)
•Recovery of walking function is one of the main goals of patients after stroke.•RAGT may be considered a valuable tool in improving gait abnormalities.•The earlier the gait training starts, the better the motor recovery. Studies about electromechanical-assisted devices proved the validity and effectiveness of these tools in gait rehabilitation, especially if used in association with conventional physiotherapy in stroke patients. The aim of this study was to compare the effects of different robotic devices in improving post-stroke gait abnormalities. A computerized literature research of articles was conducted in the databases MEDLINE, PEDro, COCHRANE, besides a search for the same items in the Library System of the University of Parma (Italy). We selected 13 randomized controlled trials, and the results were divided into sub-acute stroke patients and chronic stroke patients. We selected studies including at least one of the following test: 10-Meter Walking Test, 6-Minute Walk Test, Timed-Up-and-Go, 5-Meter Walk Test, and Functional Ambulation Categories. Stroke patients who received physiotherapy treatment in combination with robotic devices, such as Lokomat or Gait Trainer, were more likely to reach better results, compared to patients who receive conventional gait training alone. Moreover, electromechanical-assisted gait training in association with Functional Electrical Stimulations produced more benefits than the only robotic treatment (−0.80 [−1.14; −0.46], p > .05). The evaluation of the results confirm that the use of robotics can positively affect the outcome of a gait rehabilitation in patients with stroke. The effects of different devices seems to be similar on the most commonly outcome evaluated by this review.